Forensic podiatry principles and methods - DiMaggio, John A.; Vernon, Wesley; SpringerLink (Online service). (New York Humana Press, 2011)
The human foot is a complex body part composed of fifty-two bones, which is twenty-five percent of all the bones in the body. Nonetheless, the foot is often viewed by the public and doctors as a 'minor' body part. Similarly, the importance of pedal evidence in crime investigation has also long been undervalued, but as footwear evidence has become more commonly used in forensic situations, so has pedal evidence, which is why this seminal work is so important: it is the first textbook ever dedicated to forensic podiatry. "Forensic Podiatry" is an international compilation of current pr.
Part 1. General Forensic Concerns -- The Crime Scene and Crime Laboratory -- Forensic Podiatry Principles and Human Identification Part 2. Podiatric Forensic Concerns -- Photographic Techniques -- Bare Footprint Identification -- Footwear Examination and Analysis -- Forensic Gait Analysis -- Identification from Podiatry Records -- Part 3. Pedal case work -- Case Studies in Forensic Podiatry -- Part 4. Medicolegal Concerns -- Expert Witness Considerations and Standards of Practice.
Includes bibliographical references and index.
Keywords: Electronic books